2016
DOI: 10.1103/physreva.93.033801
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent fluctuations of intermittent resonance fluorescence

Abstract: Electron shelving gives rise to bright and dark periods in the resonance fluorescence of a threelevel atom. The corresponding incoherent spectrum contains a very narrow inelastic peak on top of a two-level-like spectrum. Using the theories of balanced and conditional homodyne detection we study ensemble averaged phase-dependent fluctuations of intermittent resonance fluorescence. The sharp peak is found only in the spectra of the squeezed quadrature. In balanced homodyne detection that peak is positive, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 34 publications
(90 reference statements)
2
24
0
Order By: Relevance
“…Actually, in the linear response limit the drive term can be neglected from the coherent dynamics [63], which is really useful for the numerical calculation of the transmission spectrum. On the other hand, if our scheme is implemented in a cavity-QED setup, the fluorescence spectrum of the quantum probe could be measured using, for example, the standard balance homodyne detection schemes [50]. In this technique the phase of the unknown signal is measured by mixing it with a strong local oscillator (LO) in a beam splitter, where the LO is a field with a well-define amplitude and phase.…”
Section: Experimental Relevancementioning
confidence: 99%
“…Actually, in the linear response limit the drive term can be neglected from the coherent dynamics [63], which is really useful for the numerical calculation of the transmission spectrum. On the other hand, if our scheme is implemented in a cavity-QED setup, the fluorescence spectrum of the quantum probe could be measured using, for example, the standard balance homodyne detection schemes [50]. In this technique the phase of the unknown signal is measured by mixing it with a strong local oscillator (LO) in a beam splitter, where the LO is a field with a well-define amplitude and phase.…”
Section: Experimental Relevancementioning
confidence: 99%
“…This issue has been highlighted both theoretically [23,26] and experimentally [24] in the context of cavity QED systems and subsequently, also theoretically, in resonance fluorescence of a three level atom [37]. Still more recently, Castro-Beltrán et al [38][39][40][41] undertook a thorough analytical treatment of non-Gaussian fluctuations encountered in resonance fluorescence of two-and three-level atomic systems via intensity-field correlation measurements. Further context-dependent studies on the subject have also been reported, such as the light emitted from a two-level atom in an optical cavity [42,43], superconducting artificial atoms [44], fluorescence from optical transitions in Ξ-and V-type three-level atoms [45,46], and the experimental realization of the resonance fluorescence of a single trapped 138 Ba + ion [47].…”
Section: Conditional Homodyne Detectionmentioning
confidence: 99%
“…In general, the Bloch equations are solved numerically. However, accurate approximate analytical solutions in the resonant case, ∆ = 0, in the regime (9) were obtained by two of us in [7]. The populations and coherences show the typical short-term decay at the rate 3γ + /4 reminiscent of the 2LA dynamics and a long-term decay, at roughly γ a , that signals shelving in the metastable state |a [4].…”
mentioning
confidence: 98%
“…Because of the pure spontaneous emission decay, the incoherent nature of the |e − |a − |g channel decouples the equations for the coherences involving the |a state from those of the laser driven |e − |g transition [7,12]. The Bloch equations of the effective two-level system can then be written in compact form as…”
mentioning
confidence: 99%
See 1 more Smart Citation